Immune-Replacement Therapy in the Complex Treatment of Acute Lung Injury in Patients with Severe Sepsis - K. B. Grigoryev; S. I. Apevalov; A. E. Matyukov; L. V. Okhinko (Общая реаниматология)
Objective: to improve the results of intensive care in patients with acute lung injury in the presence of severe sepsis. Subjects and methods. Complex intensive therapy was analyzed in 87 patients with severe sepsis and acute lung injury. The patients were divided into 2 groups: 1) 43 patients treated without immune-replacement therapy; 2) 44 were additionally given the intravenous immunoglobulin G Gamimun H. The laboratory parameters, mortality, and intensive care duration in an intensive care unit (ICU) were analyzed. Results. Immune-replacement therapy reduced the length of stay in the ICU from 15±5.5 to 11.5±4.4 days and mortality from 55.8 to 27.3%. Conclusion. The immunoglobulin G Gamimun (BAYER) used in patients with acute lung injury in the presence of severe sepsis has shown its high efficacy, quality, and safety. Key words: sepsis, acute lung injury, immunoglobulins, Gamimun.